2015
DOI: 10.1007/s13277-015-3051-9
|View full text |Cite
|
Sign up to set email alerts
|

SOX4 overexpression is a novel biomarker of malignant status and poor prognosis in breast cancer patients

Abstract: Sex-determining region Y-related high mobility group box 4 (SOX4) has been proven to serve as a critical role in cancer development and progression. However, little is known about the pathological role of SOX4 in breast cancer patients. The purpose of this study is to measure the expression of SOX4 in breast cancer patients and to explore the clinical significance of SOX4. Using RT-PCR and Western blot, messenger RNA (mRNA) and protein expression of SOX4 were measured in breast cancer tissues and adjacent norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…5a heat map and Supplementary Table 2), the progenitor transcription factor Sex-Determining Region Y-box4 (SOX4) caught our attention for the following reasons: (1) its expression exhibited the greatest fold-change upon both knockdown and overexpression of GALNT14 ; (2) SOX4 has been shown to be regulated by BMP signalling, which was identified as a target pathway of GALNT14 in the current study; and (3) increased SOX4 expression in glioma-initiating cells has been reported37. In breast cancer, SOX4 is associated with cancer progression25383940, yet its role during the metastasis initiation step remains unclear. Furthermore, the contribution of GALNTs to pulmonary metastasis through the regulation of SOX4 is unknown.…”
Section: Resultsmentioning
confidence: 74%
“…5a heat map and Supplementary Table 2), the progenitor transcription factor Sex-Determining Region Y-box4 (SOX4) caught our attention for the following reasons: (1) its expression exhibited the greatest fold-change upon both knockdown and overexpression of GALNT14 ; (2) SOX4 has been shown to be regulated by BMP signalling, which was identified as a target pathway of GALNT14 in the current study; and (3) increased SOX4 expression in glioma-initiating cells has been reported37. In breast cancer, SOX4 is associated with cancer progression25383940, yet its role during the metastasis initiation step remains unclear. Furthermore, the contribution of GALNTs to pulmonary metastasis through the regulation of SOX4 is unknown.…”
Section: Resultsmentioning
confidence: 74%
“…In the study of human breast cancer, SOX4 was overexpressed and correlates with (ER-/PR-/ HER2-) subtype of breast cancer. Further research found SOX4 can promote the progression of breast cancer by regulating epithelial-mesenchymal transformation (EMT) [47]. Other studies indicated that SOX4 was overexpressed in bladder tumor [48] and hepatocellular carcinoma [49] and it can regulate EMT to promote metastasis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Bilir et al demonstrated that SOX4 promoted tumor initiation and development in prostate cancer [25]. Song et al documented that SOX4 was associated with malignant status of breast cancer [42]. Lin et al showed that high expression of SOX4 was associated with poor outcome of colon cancer patients [26].…”
Section: Discussionmentioning
confidence: 99%